ANALISIS KEMAMPUAN LITERASI NUMERASI DITINJAU DARI MOTIVASI BELAJAR SISWA SMAN 1 BARAT - Affiah, Eva Nur Amalia Chofifatul; Khasanah, Lintang Sekar; Firdaus, Tiara Citra Maharani; Febita, Ferry; Apriandi, Davi; Setyansah, Reza Kusuma (LPPM Universitas Bina Bangsa, 2024)
Literacy and numeracy skills are essential skills that students must master starting from the primary school level. Motivation is a psychological condition in a person who is driven by a strong will and presents a feeling of pleasure in carrying out an action to achieve a certain goal. So this research aims to describe numeracy literacy skills in terms of student learning motivation. This research is descriptive qualitative research. The data collection technique used questionnaires, tests, and interviews. So the conclusion of this study is that the numeracy literacy skills of students with high learning motivation, moderate learning motivation and low learning motivation in solving problems are similar, numeracy literacy skills of students with high learning motivation and moderate learning motivation also have similarities in determining and implementing appropriate solution strategies, while literacy and numeracy skills of students with low learning motivation, in determining and implementing strategies and solutions are not appropriate